2015
DOI: 10.1111/jocn.12890
|View full text |Cite
|
Sign up to set email alerts
|

Supporting new graduate nurses making the transition to rural nursing practice: views from experienced rural nurses

Abstract: The findings can be used by rural health services and experienced rural registered nurses to assist in implementing adequate and timely support for new graduate nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 15 publications
(38 reference statements)
0
66
0
Order By: Relevance
“…To further exacerbate this intense period, it appeared that the senior nurses had unrealistic expectations of the new graduates. New graduates in the rural sector were expected to “hit the ground running,” accept full responsibility for patients and to be accountable for a full patient load as soon as possible, with little support when left as the only registered nurse on the ward (Lea & Cruickshank, , , ). The responsibility of the new graduate nurse extended to supervising nursing students early in their graduate programme which only served to prolong their feelings of transition shock (Lea & Cruickshank, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further exacerbate this intense period, it appeared that the senior nurses had unrealistic expectations of the new graduates. New graduates in the rural sector were expected to “hit the ground running,” accept full responsibility for patients and to be accountable for a full patient load as soon as possible, with little support when left as the only registered nurse on the ward (Lea & Cruickshank, , , ). The responsibility of the new graduate nurse extended to supervising nursing students early in their graduate programme which only served to prolong their feelings of transition shock (Lea & Cruickshank, ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the shortage of staff in rural areas and inadequate skill mix, orientation was not often delivered and one‐on‐one support was absent at the ward level (Lea & Cruickshank, , ; Mellor & Greenhill, ). New graduates found that clinical support was ad hoc or that they had to search for support (Lea & Cruickshank, , , ; Mellor & Greenhill, ; Ostini & Bonner, ) what Johnstone, Kanitsaki and Currie (as cited in Lea & Cruickshank, ) refer to as “self‐support.” Studies from NSW revealed that when the new graduates asked for support, they were met with friendly and helpful staff; however, self‐support was only successful if the new graduates knew when they needed clinical support and if they were confident enough to ask (Lea & Cruickshank, , , ). The success of self‐support also varied depending on senior staff working on a shift with the new graduates and not all staff were approachable (Lea & Cruickshank, , , ; Mellor & Greenhill, ; Ostini & Bonner, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their stress as qualified nurses comes from excessive workload in the ward. [7,8] They also express challenges in managing and prioritizing routine work and heavy workloads in the first few months. [3,6] Another study showed that the nurses working in general medical or surgical wards have high stress levels due to heavy workloads.…”
Section: Literature Reviewmentioning
confidence: 99%